Caracterização sócio-ambiental do bairro de Felipe Camarão- Natal/ RN - Bezerril, Sandra Maria de Lima (2006)
The rapid growth of the Brazilian cities in the latest years has brought a series of problems regarding housing policies and, therefore, the provision of dwellings for the low-income class people. Following the pattern of other capital cities, Natal has repeated the pattern of urbanization practiced in the country, which concentrates the low-income class inhabitants in specific zones of the city known as peripheries or even in a dwelling place for less-favored classes such as Felipe Camarão, which is one of ten boroughs belonging to the western administrative zone, a region which has historically received less attention from the public administrators towards infrastructure investments. Based on those aspects, the general objective of this work is to investigate which main social-environmental alterations have resulted from the processes of urbanization and field occupation in that area. The specific objectives are concerned with verifying 1) the process of urbanization and the process of dividing urban soil from the 1960s; 2) the current configuration of the public spaces in the borough; 3) the process of the deprivation of the original landscape characteristics of Environmental Protection Zones; 4) the dynamics of land occupation which are predominant in dune areas; 5) the dynamics of land occupation which are predominant in mangrove areas; 6) and the destruction of green covering on the land with its consequent alteration of the local floristic pattern. The methodology consisted of in-loco visits; the application of questionnaires as community research; a survey of bibliography published by the organisms and institutions in charge of carrying out the city hall s environmental and housing policies; and descriptive statistics of the collected data. Concerning the pattern of occupation which is predominant in the borough, the treatment of space dispensed by the local dwellers has culminated in the emergence and consolidation of environmental alterations which are clearly different from common occurrence in both the building area represented by housing complexes and in the green areas represented by dunes and mangroves. The data show that there was the predominance of the irregular land occupation process over the official housing policy during the population settlement which contributed with a series of frequent and foreseeable problems in the dynamics of urbanization of poverty such as invasions and appropriations of land parcels, the beginning of irregular arrangement of streets, the formation of villages and slums, which are full of self-constructed housing units, and the occupation and degradation of susceptibly fragile environmental areas such as the dune slopes and the mangroves